Potensi dan Mekanisme Yeast-Like Fungus Pseudozyma dalam Mengendalikan Antraknosa pada Cabai - Sri Hartati; Suryo Wiyono; Sri Hendrastuti Hidayat; Meity Suradji Sinaga (Universitas Bangka Belitung, 2023)
Application of biocontrol agents on pre- and post-harvest commodities is a promising disease control strategy. This research was objected to study the potencies and antagonism mechanisms of eight isolates of yeast-like fungus Pseudozyma, i.e. P. hubeiensis Dmg 18 BEP, Dmg 20 DEP, Dmg 23 DEP, Dmg 27 BEP, and Dmg 32 DEP, P. shanxiensis Dmg 28 DEP, dan P. aphidis SG 25 BE and SG 53 BE in controlling Colletotrichum acutatum, the cause of anthracnose on chili. Those isolates of Pseudozyma were obtain from chili leaf and fruit surfaces and tissues. To study their potencies in controlling anthracnose on chili caused by C. acutatum, the eight Pseudozyma isolates were applied on chili fruit. While the study of the antagonism mechanisms was performed by antibiosis, volatile compound formation, chitinolitic activities, hyperparasitism, and ACC deaminase production tests. The results showed that all isolates of the Pseudozyma had the potencies to control anthracnose on chili caused by C. acutatum with more than 60% control levels. The mechanisms were production of volatile compounds, chitinolitic activities, and hyperparasitism. Those Pseudozyma isolates did not produce ACC deaminase.